THE EFFECTIVENESS OF MENTOR COACHING ON PREPARING TEXT-BASED LESSON PLAN BY STUDENT TEACHERS - Amalia, Lulu Laela; Rodliyah, Rojab Siti (Jurnal Bahasa Lingua Scientia, 2019)
This paper will present the result of the study aimed at investigating the impact of online mentor coaching strategy on the process of making Text-Based Lesson Plan by student teachers using Edmodo. The participants were students who are going to conduct field practice in the following year. The study was descriptive qualitative in nature and the data were obtained from the observation, documents (students? lesson plan) and interview. The result showed that the student teachers responded positively on the use of Edmodo because of its flexibility. They prefer consulting through Edmodo because it enhances their confidence and their final Lesson Plan can be implemented well during the micro teaching.